O habitus dos gestores e a adoção de sistemas de informação : estudos de caso em cooperativas agroindustriais do Paraná - Freitag, Viviane da Costa (Universidade do Vale do Rio dos Sinos, 2019)
This thesis aims to analyses how the managers’ habitus can explain the information system’s (IS) adoption. Holds that habitus, is characterized by agent’s capital and can explain the adoption of organizational IS. Adoption studies are considered a mature academic field, these studies are habitus by psychology and behavioral theories, which lacks between potential use and use of technologies and do not contemplate mandatory adoption, when agents have no options to decide if adopt or not a system. Moreover, this study is grounded on Action Theory, which concerns that the subject is embodied with a practical sense, the habitus, which drives his choices. This subject, who has habitus, is inserted in a social space called the field, which him structure and is structured by it. The Action Theory is substantial to IS adoption studies, which focus on the relationship and distinction by agents, who origins their practices. Qualitative research conduces analyses by the interpretative vision, embodied theoretical and structuralist constructivist present by Bordieu and systematized by Thiry-Cherques, divided in three steps: Theorization, investigation and critics. Uses field research strategy and case study. The data collected was made by interviews, documents and secondary data. The number of selected agents comprise 25 managers who act at distinct hierarchical levels in two agroindustrial cooperatives located in the western mesoregion of Paraná and are recognized by holds symbolic and economic capital. The results indicated that the conscious and condition existence are constituted by, ethnicity, family, religion, as well as the path in a cooperative and social relationships in the field, these elements are formative characteristics of social capital and contribute to habitus progress. Agents acquired Cultural capital by the path taken in a cooperative, and this capital urges the IS adoption. Managers knows their action limits, so understanding the needs required by their activities, makes the use of IS a process of grounded decision making. The agents who knows cooperatives process and particularities can adapt to solve problems and bring new solutions. Those agents, detent an ethos of commitment, loyalty, honesty, persistency, and other values which conducts the cooperative alignment. This thesis concludes that the decision makers habitus explains IS adoption, once what brings these practices is formed by symbolic capital, creating a relationship who structures and is structured by cooperatives.
Keywords: Habitus; Gestores; Adoção; Sistemas de Informação; Cooperativas Agroindustriais; Habitus; Manager; Adoption; Information Systems; Agroindustrial Cooperatives; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis